2019
DOI: 10.1155/2019/7349135
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in relation to Gender, Teaching Experience, and Educational Level among Educators

Abstract: This study aims to investigate the burnout levels of the educators with respect to gender, teaching experience, and educational level. The subjects of the study are 31 educators. A survey design using a questionnaire was utilized to collect data within three burnout dimensions, i.e., emotional exhaustion (EE), depersonalization (DP), and reduced personal accomplishment (PA). The study has found that the educators are emotionally exhausted and experience reduced personal accomplishment levels with high levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 10 publications
1
29
0
2
Order By: Relevance
“…In line with the growing interest in aspects related to flourishing in teaching, the aim of this study is to examine the mediating role of flourishing in the relationship between PsyCap and the three burnout dimensions, namely emotional exhaustion, depersonalization, and a lack of professional accomplishment (see Figure 1). explanation of burnout, with greater vulnerability to the syndrome in the higher educational stages [52,53] and in teachers with little experience [54,55].…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the growing interest in aspects related to flourishing in teaching, the aim of this study is to examine the mediating role of flourishing in the relationship between PsyCap and the three burnout dimensions, namely emotional exhaustion, depersonalization, and a lack of professional accomplishment (see Figure 1). explanation of burnout, with greater vulnerability to the syndrome in the higher educational stages [52,53] and in teachers with little experience [54,55].…”
Section: The Current Studymentioning
confidence: 99%
“…Women would be more likely to suffer emotional exhaustion while men would be more affected by depersonalization and a lack of professional accomplishment [ 47 , 48 , 49 , 50 , 51 ]. The educational stage and professional experience may also be significant factors in the explanation of burnout, with greater vulnerability to the syndrome in the higher educational stages [ 52 , 53 ] and in teachers with little experience [ 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the ongoing education reform of the country in line with the increase of globalization effects. These rapid changes have added teachers' responsibilities apart from their teaching roles (Izzul & Huay, 2019). This is also stated by Frankie and Macdonald (2016) found that teachers' burnout also due to the high expectation or demands of the administrators.…”
Section: Introductionmentioning
confidence: 86%
“…In the extant literature, some researchers indicate that gender impacts job performance (Burleson & Samter, 1992 ; King et al, 2010 ; Nasir et al, 2011 ) and personal accomplishment levels of people (Jamaludin & You, 2019 ). Compared to women, the sense of personal accomplishment and job performance is more prominent in men (Kacmar et al, 2011 ).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%